Examining Motivational Orientation and Learning Strategies in Computer-Supported Self-Directed Learning (CS-SDL) for Mathematics: The Perspective of Intrinsic and Extrinsic Goals. (January 2017) - Lao, Andrew Chan-Chio; Cheng, Hercy N. H.; Huang, Mark C. L.; Ku, Oskar; Chan, Tak-Wai
One-to-one technology, which allows every student to receive equal access to learning tasks through a personal computing device, has shown increasing potential for self-directed learning in elementary schools. With computer-supported self-directed learning (CS-SDL), students may set their own learning goals through the suggestions of the system based on their e-portfolio and strive for the goals with efforts and mathematics capability. However, unlike adults who hold specific purposes that lead to enhanced motivation for SDL, children's motivation is crucial for learning individually. Therefore, this study examines the differences in motivational orientation and learning strategies between second graders with different intensities of intrinsic and extrinsic goals. The results indicate that students with high intensity of both intrinsic and extrinsic goals demonstrate significantly higher motivational orientation and learning strategies than those with low intensity of goals. These results provide supportive evidence for the design of CS-SDL at the elementary level and offer a reference for exploring children's motivational differences in CS-SDL.